Planetary ball-mill as a versatile tool to controlled potato starch modification to broaden its industrial applications - Juárez Arellano, Erick Adrián; Urzúa Valenzuela, Michell; Peña Rico, Miguel Angel; Aparicio Saguilan, Alejandro; Valera Zaragoza, Mario; Huerta Heredia, Ariana Arlene; Navarro Martinez, Ana Karin (Food Research International, 2021)
Pure potato starch has been modified by high-energy-ball-milling as a function of energy supplied, aiming to obtain products for different possibilities of industrial application. Burgios's equation has been used to calculate the energy supplied. The effect of the milling has been followed by a characterization of the starch morphology, crystallinity, solubility, swelling, retrogradation, viscosity, apparent viscosity, functional groups, and reducing sugar concentration. The high-energy-ball-milling not only changes the physical properties but also induces the mechanolysis of potato starch, breaking the glycosidic linkages of the starch molecules. A representation of the possible mechanism of starch mechanolysis is proposed. Three stages of the transformation of potato starch through high-energy ball-milling can be identified. Each of these stages generates starch with properties that can be used in different industrial applications.
Keywords: Almidón de papa; Molienda mecánica de alta energía; Aplicaciones industriales